Pathways and Patterns of Cell Loss in Verified Alzheimer’s Disease: A Factor and Cluster Analysis of Clinico-Pathological Subgroups - H. Förstl; R. Levy; A. Burns; P. Luthert; N. Cairns (Behavioural Neurology)
Thirty-seven patients with neuropathologically verified Alzheimer's disease (AD) have been studied prospectively. A principal components analysis of neuron numbers in cortical and subcortical areas revealed two variables: Variable I with high loadings for the hippocampo-parahippocampo-parietal neuron counts and Variable II with high loadings for coeruleo-frontal cell numbers. Both may reflect functional neuroanatomical connections which may act as pathways of neurodegeneration in AD. A cluster analysis based on these neuron numbers yielded three groups of patients: Cluster A with low hippocampo-parahippocampo-parietal cell counts, Cluster B with well-preserved neuron numbers, and Cluster C with low coeruleo-frontal neuron numbers. Differences in clinical features between these patient groups indicated the potential clinical relevance of these clusters.